RANCANGAN PENYULUHAN TENTANG EFISIENSI PEMASARAN DAGING SAPI DI PASAR TRADISIONAL KOTA PROBOLINGGO - Arief Reza Wahyudi; Novita Dewi Kristanti; Hananik Prasetyo (Jurnal Pemantik, 2022)
This study aims to compile the Design of Counseling on the Efficiency of Beef Marketing Channels in the Traditional Markets of Probolinggo City. The study method uses descriptive quantitative methods. The population in this study were traditional markets, slaughterhouses and livestock groups in the city of Probolinggo. Determination of the sample using snowball sampling technique and purposive sampling. The results of the study show that there are 4 marketing channels in the traditional markets of the city of Probolinggo, namely (1) Farmers - Butchers - Consumers, (2) Farmers - Butchers - Retailers - Consumers, (3) Cattle Traders (Belantik) - Butchers Entrepreneurs - Consumers, (4) Cattle (Belantik) Traders - Butchers - Retailers - Consumers. The four channels have been efficient based on the calculation of farmer's share, the first channel is the most efficient channel with a farmers share value of 54.87%. Every 1 increase in the number of marketing agencies will increase the marketing margin by Rp. 10,097,979. Every 1% increase in the efficiency of the marketing channel will increase the margin of the marketing channel by Rp. 1,411,984. The extension design was based on the material from the study results using a media folder with the lecture and discussion method in the Bango Jaya cattle group. The results of the evaluation of outreach activities on farmer attitudes which consist of Receiving, Responding, Assessing, Organizing, and Characteristics based on the values classified as positive or showing a good attitude with a percentage of 100%.